Re-evaluation of the Permian macrofossils from the Parnaíba Basin: Biostratigraphic, palaeoenvironmental and palaeogeographical implications - Iannuzzi, Roberto; Neregato, Rodrigo; Cisneros, Juan C.; Angielczyk, Kenneth D.; Rößler, Ronny; Rohn, Rosemarie [UNESP]; Marsicano, Claudia; Fröbisch, Jörg; Fairchild, Thomas; Smith, Roger M.H.; Kurzawe, Francine; Richter, Martha; et al. (Geological Society of London, 2018)
Although Permian fossils have been known from the Parnaíba Basin for two centuries, and some faunal and flora elements are well known worldwide, research on the fossil assemblages from this basin has lagged relative to other, more accessible basins. In the last decade, however, there has been a significant increase in the study of fossils from the two Permian units of the basin: the Pedra de Fogo and Motuca formations. The goal of this contribution is to synthesize and update the existing data on the Permian macrofossils from these formations, and to use them to address biostratigraphic, palaeoenvironmental and palaeogeographical questions. The Pedra de Fogo and Motuca formations are likely to be Cisuralian in age. Contrary to previous reports, there is more than one stratigraphic interval that preserves petrified fossil plants. The possible marine influence proposed for the Pedra de Fogo Formation must be reassessed based on the strongly terrestrial character of its fossil assemblages. Palaeoenvironmental and palaeoclimatic conditions are inferred to be wetter than is typically predicted for this region of the globe based on climatic modelling. Despite sharing some taxa with the Euramerican and Gondwanan biogeographical provinces, the Parnaíba Basin was likely to have been part of a distinct biogeographical province, as indicated by the high degree of endemism displayed by its Permian floras and faunas.